Anglo-American relations in the twentieth century : of friendship, conflict, and the rise and decline of superpowers - Dobson, Alan P. (British history in perspective., 1995)
Dobson's concise and readable book covers the whole of this century and employs selected historical detail to expose the special relationship between Britain and America in its true light.